2010
DOI: 10.1111/j.1365-2834.2010.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of role competencies for Chinese directors of nursing based on the forces of magnetism

Abstract: The study's findings support the transferability of the Forces of Magnetism to nursing management in hospitals internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…RNs evaluated their nurse managers’ TL qualities slightly higher than nurse directors. This has been found in previous studies (Eneh et al, ; Kvist et al, ; Spicer et al, ). As in described in Figure , nurse directors are more far from RNs, while nurse managers are front line managers in Finland.…”
Section: Discussionsupporting
confidence: 88%
“…RNs evaluated their nurse managers’ TL qualities slightly higher than nurse directors. This has been found in previous studies (Eneh et al, ; Kvist et al, ; Spicer et al, ). As in described in Figure , nurse directors are more far from RNs, while nurse managers are front line managers in Finland.…”
Section: Discussionsupporting
confidence: 88%
“…They have to bear all the responsibility for their decisions and be able to cope with stressful situations. The most important role-specific competencies for the Unauthenticated Download Date | 5/11/18 11:28 PM first leadership level are a positive attitude towards education and good interprofessional relationships (Fukurawa & Cunha, 2011;Spicer et al, 2011). The results of our research show that the similarity of competency norms in state administration and nursing care is greatest at this leadership level.…”
Section: Discussionsupporting
confidence: 53%
“…However, the results are aligned with several previous studies; Scott (2007) reported that only 10.3% of NAs had a master’s degree. In China, about 6.7% of DONs had graduate education (Spicer et al. 2011).…”
Section: Discussionmentioning
confidence: 99%